Internal control weaknesses: Its relationship with local government characteristics and follow-up on audit results - Dwi Nurmala Sari; Dewi Darmastuti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
Internal control plays a critical role in achieving the effectiveness and efficiency of organization's operational activities. This study seeks to investigate the effect of local government size, locally-generated revenue, capital expenditures, social assistance expenditures, and follow-up audit results on local government’s internal control weaknesses. By using multiple linear regressions on 382 samples of local governments in Indonesia, this study found that local government size and social assistance expenditures positively affected internal control weaknesses. Locally-generated revenue negatively affected internal control weaknesses, while capital expenditures and follow-up audit results did not significantly affect internal control weaknesses. This study adds social assistance expenditures, which are still rarely studied by previous researchers because of the large number of irregularities and their discretionary nature. Thus, the results of this study may provide an input for auditors and regulators to focus more on spending on social assistance and further improve comprehensive standards in internal control systems.